Stan nietrzeźwości poszkodowanego a prawo do jednorazowego odszkodowania z tytułu wypadku przy pracy rolniczej - Puślecki, Damian (Wydawnictwo Naukowe UAM, 2008)
The purpose of the paper is to resolve some of the issues arising from the exemption of the right to one-off indemnity for an agricultural accident due to insobriety of the injured party. The manner in which insobriety of the injured party is measured and assessed as well as the conditions in which the injured party is denied indemnity are being analysed. In the conclusions the author claims that the provisions that determine the premises on the grounds of which the right to one-off indemnity may be exempted remain unclear. This leads to numerous legal actions being taken into courts. The most important part of the proceedings performed after an accident is proper and duly performed assessment o f the sobriety of the injured party with a view of establishing that party's contributory negligence leading to the accident. The state of insobriety does not always result in the exemption of the right to one-off indemnity, which may only be denied when a significant causational link has been determined between the insobriety o f the injured party and the agricultural accident. In the author's opinion, since the accident insurance plays a protective role, it is necessary to precise the criteria that may lead to the exemption of the intoxicated injured party from the entitlement to a one-off indemnity for an agricultural accident.

L ’obiettivo dell’articolo é la risoluzione dei problemi giuridici riguardanti l’esclusione del diritto al risarcimento per infortunio sul lavoro agricolo a causa dello stato di ebbrezza del danneggiato. In particolare, oggetto dell’analisi sono le questioni concernenti la nozione di stato di ebbrezza delle vittime dell’infortunio e le condizioni alie quali viene meno il diritto alia prestazione da parte delle assicurazioni contro l’infortunio. In conclusione L’Autore constata che le norme che determinano i presupposti per l’esclusione del diritto al risarcimento non sono sufficientemente ehiare, ció causa numerosi ricorsi in tribunale. La questione piú importante in materia é l’adeguata determinazione dello stato di ebbrezza del danneggiato e la valutazione dell’influenza di tale stato nella causazione dell’incidente. Lo stato di ebbrezza non sempre comporta l’esclusione del diritto alia ricompensazione. Ció succede solo nei confronti del danneggiato che, trovandosi nello stato di ebbrezza, ha contribuito al verificarsi dell’incidente in modo significante. Secondo l’Autore, considerando la funzione di protezione delle assicurazioni contro l’infortunio, sarebbe necessaria un’ulteriore precisazione dei criteri di esclusione del diritto al risarcimento nei casi de quo.
Insobriety of the injured party and a right to one-off indemnity for an agricultural accident
Lo stato di ebrezza del danneggiato e il diritto al risarcimento per infortunio sul lavoro agricolo